Effect of a rectangular tunnel in the foundation soil on the seismic response of dikes - Teheri, Kelvin (2017)
The project describes a parametric study of a simulation using PLAXIS 2D 2015 software. The objective of the project is to investigate the effect of the size and the location of a rectangular tunnel or hole in the foundation soil on seismic responses. In this project, square is chosen for simplicity. To determine the critical horizontal displacements and Peak Ground Accelerations (PGA) of the dike during the earthquake loading phase, various variables of sizes and locations of a rectangular tunnel will be inputted into the PLAXIS 2D.